Following the use of educational units based on the Zahorik model in teaching some wrestling holds to freestyle wrestlers aged (12-14) years - فائق, أ.م.د. علي فؤاد (Sulaimani Journal for Humanities, 2026)
This research aims to: 1- Develop training units based on the Zahorik model to teach wrestling holds to freestyle wrestlers aged 12-14 years. 2- Determine the effect of training units based on the Zahorik model on the learning of wrestling holds by freestyle wrestlers aged 12-14 years. The experimental method was used, and the research sample was selected from wrestlers at Al-Adhamiya Sports Club for the 2024/2025 season. The Statistical Package for the Social Sciences (SPAS) was used to extract statistical data. The results showed that the training units based on the Zahorik model had a positive effect on the learning of wrestling holds by freestyle wrestlers. It was recommended that coaches be encouraged and supported to use these modern methods in the teaching process.
Keywords: Zahorik Model; Wrestling Grips